METHODOLOGY OF USING INNOVATIVE TECHNOLOGIES IN TEACHING PHYSICS - Seytimbetova Gulbadan Azatovna; Embergenova Kamila Aytbaevna (Bright Mind Publishing, 2025)
The process of teaching physics in higher education is one of the important aspects of the modern education system. Physics, with its place among the natural sciences, helps students understand the laws of nature, study physical processes and understand their application in practice. However, today the use of innovative technologies in the educational process is becoming increasingly important in teaching physics. This article provides information on how to effectively use innovative technologies in teaching physics in higher education.
Keywords: Physics, innovative technologies, students, methods, research, presentations, videos, simulations, interactive programs.